Handbook of energy efficiency and renewable energy - Kreith, Frank; Goswami, D. Yogi (Mechanical engineering series (Boca Raton, Fla.), 2007)
Brought to you by the creator of numerous bestselling handbooks, the Handbook of Energy Efficiency and Renewable Energy provides a thorough grounding in the analytic techniques and technological developments that underpin renewable energy use and environmental protection. The handbook emphasizes the engineering aspects of energy conservation and renewable energy. Taking a world view, the editors discuss key topics underpinning energy efficiency and renewable energy systems. They provide content at the forefront of the contemporary debate about energy and environmental futures. This is vital information for planning a secure energy future. Practical in approach, the book covers technologies currently available or expected to be ready for implementation in the near future. It sets the stage with a survey of current and future world-wide energy issues, then explores energy policies and incentives for conservation and renewable energy, covers economic assessment methods for conservation and generation technologies, and discusses the environmental costs of various energy generation technologies. The book goes on to examine distributed generation and demand side management procedures and gives a perspective on the efficiencies, economics, and environmental costs of fossil and nuclear technologies. Highlighting energy conservation as the cornerstone of a successful national energy strategy, the book covers energy management strategies for industry and buildings, HVAC controls, co-generation, and advances in specific technologies such as motors, lighting, appliances, and heat pumps. It explores energy storage and generation from renewable sources and underlines the role of infrastructure security and risk analysis in planning future energy transmission and storage systems. These features and more make the Handbook of Energy Efficiency and Renewable.